Research Trends in IoT-Integrated Automated Titration Systems Using Peristaltic Pump: A Bibliometric Study - Adisty Putri (Department of Physics, Universitas Negeri Padang, 2026)
This study examines research trends in IoT-integrated automated titration systems employing peristaltic pumps through a combined bibliometric analysis and Systematic Literature Review (SLR). Data were collected from the Scopus and Google Scholar database covering the period 2016-2026 and analyzed using VOSviewer to map publication trends, geographical distribution, journal contributions, and keyword co-occurrence networks. The result reveal a fluctuating yet overall increasing research trend, with peak publication activity observed 2019 and 2021. The united States and Brazil dominant research output, followed by emerging contributions from China, India, and Indonesia. Journal distribution indicates that publications are concentrated in a limited number of core outlets, particularly within analytical chemistry and chemical education. Keyword analysis identifies major themes such as titration, automatic titration, peristaltic pump, arduino, and Internet of Thigs, indicating a convergence between analytical chemistry and digital technologies. This study provides a comprehensive overview of the field, identifies research gaps, and offers insight for future developments of intelligent, IoT-based laboratory systems.